BLM Deficiency Is Not Associated with Sensitivity to Hydroxyurea-Induced Replication Stress - Kenza Lahkim Bennani-Belhaj; Géraldine Buhagiar-Labarchède; Nada Jmari; Rosine Onclercq-Delic; Mounira Amor-Guéret (Journal of Nucleic Acids)
Bloom's syndrome (BS) displays one of the strongest known correlations between chromosomal instability and a high risk of cancer at an early age. BS cells combine a reduced average fork velocity with constitutive endogenous replication stress. However, the response of BS cells to replication stress induced by hydroxyurea (HU), which strongly slows the progression of replication forks, remains unclear due to publication of conflicting results. Using two different cellular models of BS, we showed that BLM deficiency is not associated with sensitivity to HU, in terms of clonogenic survival, DSB generation, and SCE induction. We suggest that surviving BLM-deficient cells are selected on the basis of their ability to deal with an endogenous replication stress induced by replication fork slowing, resulting in insensitivity to HU-induced replication stress.